Safety of vaginal disinfection with 3% alcohol iodine solution after cesarean section: thyroid function assessment in postpartum women with no risk factors for thyroid gland - Orlicz-Szczęsna, Grażyna; Biłan, Andrzej; Zdanowska, Jolanta (Current Problems of Psychiatry, 2011)
Objective: To prospective evaluate the influences of vagina desinfection with 3% alcohol iodine solution on thyroid function in puerperium women living in areas with iodine sufficient supplementation. Study design: Thirty one females with no personal and familiar history of thyroid diseases underwent vaginal disinfection with 3% alcohol iodine solution after cesarean section. The study finished twenty eight of them. All females we sampled for TSH and FT4 before cesarean section, after one and three months respectively. Results: The mean TSH and FT4 levels of analyzed group stayed in laboratory normal range. Fourteen percent of examined puerperium women developed TSH level depresion. One patient expand overt hypothyroidism (3.5%). Conclusions: Women after administration of large amount of iodine should be under accurate control in puerperium period.